Mengajarkan Pancasila Melalui Puisi Berjudul “Pancasila Dasar Negara” Karya: Misnawati - Anwarsani Anwarsani; Erniwati Erniwati; Mahdalena Mahdalena; Apianson Apianson; Hifzatun Najmi; Suwartini Suwartini; Sri Triwindra; Anni Millasari; Devi Kristiyaningsih; Haris Fadillah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This article discusses a poem entitled "Pancasila Dasar Negara" (Pancasila as the Foundation of the State) by Misnawati, which can be an appropriate means to teach Pancasila values to students. It also discusses the messages and values contained within the poem "Pancasila Dasar Negara" by Misnawati. The research method used in the article is the analysis of the poem "Pancasila Dasar Negara" and a qualitative approach through an interview with its author, Misnawati. The results of the analysis show: (1) The ways to teach the poem "Pancasila Dasar Negara" by Misnawati can be done through: Understanding the Context, Analysis and Discussion of the Poem Text, Discussions about Pancasila Values, Understanding the Author's Experiences, Creative Activities, Integration with Other Subjects, Poetry Performances, Social Activities, and Evaluation and Reflection. (2) The poem "Pancasila Dasar Negara" by Misnawati conveys a message about the greatness and nobility of Pancasila as the foundation of the Indonesian state. The values taught are about love for the homeland, unity, and pride as citizens, as well as the importance of upholding Pancasila values as guidelines in community and national life.